Tillage System and Crop Sequence Affect Soil Disease Suppressiveness and Carbon Status in Boreal Climate - Palojärvi, Ansa; Kellock, Miriam; Parikka, Päivi; Jauhiainen, Lauri; Alakukku, Laura (Frontiers in Microbiology, 2020)
The soil borne plant pathogens cause serious yield losses and are difficult to control. In suppressive soils, disease incidence remains low regardless of the presence of the pathogen, the host plant, and favorable environmental conditions. The potential to improve natural soil disease suppressiveness through agricultural management practices would enable sustainable and resilient crop production systems. Our aim was to study the impact of autumn tillage methods and crop sequence on the soil carbon status, fungistasis and yield in boreal climate. The disease suppression was improved by the long-term reduced and no tillage management practices with and without crop rotation. Compared to the conventional ploughing, the non-inversion tillage systems were shown to change the vertical distribution of soil carbon fractions and the amount of microbial biomass by concentrating them on the soil surface. Crop sequence and the choice of tillage method had a combined effect on soil organic carbon (SOC) sequestration. The improved general disease suppression had a positive correlation with the labile carbon status and microbial biomass. From the most common Fusarium species, the predominantly saprophytic F. avenaceum was more abundant under non-inversion practice, whereas the opposite was true for the pathogenic ones. Our findings furthermore demonstrated the correlation of the soil fungistasis laboratory assay results and the prevalence of the pathogenic test fungus Fusarium culmorum on the crop cereals in the field. Our results indicate that optimized management strategies have potential to improve microbial related soil fungistasis in boreal climate.